2011
DOI: 10.1093/jmt/48.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Chorale for Persons with Chronic Mental Illness: A Descriptive Survey of Participant Experiences

Abstract: The purpose of this survey was to assess the relationship between participation in a bilingual therapeutic performance choir and the reported quality of life for persons living with a chronic psychiatric illness. The participants were 16 volunteers who ranged in age from 32-65, had a diagnosis of a major mental illness, and were members of an existing choir within a psychiatric outpatient department of a large urban general hospital. Participants completed a self-reported quality of life questionnaire designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Finally, these results compare with the study by Eyre (), where mental health consumers were asked about their experiences of music therapy via the use of a questionnaire, as opposed to focus groups used in this present study, and similarly identified benefits in mood, self‐esteem and social interaction.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Finally, these results compare with the study by Eyre (), where mental health consumers were asked about their experiences of music therapy via the use of a questionnaire, as opposed to focus groups used in this present study, and similarly identified benefits in mood, self‐esteem and social interaction.…”
Section: Discussionsupporting
confidence: 60%
“…; Hayashi et al . ), mood (Eyre ; Silverman & Marcionetti ; Silverman & Rosenow ), evoking a sense of enjoyment and having fun (Solli et al . ), enhanced self‐esteem (Covington ; Eyre ; Grocke et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some surveys and questionnaires have been conducted (e.g. Baines, 2003; Baines & Danko, 2010; Choi, 1997; Eyre, 2011; Reker, 1991; Silverman, 2006), but their predetermined focus has resulted in limited opportunities for exploring service users’ own perspectives. A few personal narratives written by users can also be found (Hibben, 1999; Tyson, 1981).…”
Section: Introductionmentioning
confidence: 99%